Physiological Foundations of Endurance in Sports Tourism and The Effects of The External Environment on The Body - Khusniddin, Boymurodov (American Journal of Bioscience and Clinical Integrity, 2026)
In Uzbekistan, there is a wide range of opportunities for sports tourism in desert, steppe and mountainous regions. The physiological basis of endurance in sports tourism and the great influence of the external environment on the body was analyzed. According to age and social characteristics, sports tourism is divided into children's tourism, youth tourism, adult tourism, family tourism, tourism for the disabled, etc.